Pengembangan Media Pembelajaran Berbasis Web untuk Bahasa Inggris di Sekolah Dasar - Muh. Hafidz; Rasmiati Rasyid; I Gede Purwana Edi Saputra (Perhimpunan Ahli Teknologi Informasi dan Komunikasi Indonesia, 2024)
This study seeks to create web-based interactive learning media to improve students' comprehension of the Simple Past Tense and Simple Future Tense at SDN 1 Lamoiko. The material was created utilizing the ADDIE development paradigm (Analyze, Design, Development, Implementation, Evaluation) and web technologies like PHP, HTML, CSS, and JavaScript. Evaluation was performed by User Acceptance Testing (UAT) and N-Gain analysis to assess the efficacy of the medium. The UAT results indicated a teacher satisfaction rating of 85%, classified as